Advances of Various Heterogeneous Structure Types in Molecular Junction Systems and Their Charge Transport Properties (Adv. Sci. 30/2022). Issue 30 (25th October 2022) - Shin, Jaeho; Eo, Jung Sun; Jeon, Takgyeong; Lee, Takhee; Wang, Gunuk
Abstract : Molecular Heterostructures In article number 2202399, Takhee Lee, Gunuk Wang, and co‐workers present recent advances to develop a wide spectrum of heterostructures in molecular junctions, as well as their prospects and applicability. Various types of two‐ and three‐terminal molecular heterostructures and their novel electrical characteristics, along with their charge transport mechanisms are presented. In addition, the potential applicability, merits, and perspectives of molecular heterojunction structures, as well as the anticipated challenges and issues their implementation in electronic device applications are discussed.